(untitled) (AYUSHDHARA, 2022)
Ayurveda is oldest medical science known to mankind and mainly aims at healthy living and long life unlike other medical science which simply focus on the treatment of diseases and secondary disorders. In a Visa (poisoning) condition not diagnosed properly or no treated in properly in their earlier stages it will leads manifestation of Visopadrava (secondary disorders). Visopadrava plays very important role in diagnosis, prognosis and treatment of the diseases. Hence in the present article effort is made to understand the concept of Visopadrava with betterment approach proper treatment and Pathya-Apathya.